Benign mesenchymal tumours and tumour‐like lesions in end‐stage renal disease. Issue 2 (28th September 2012) - Büttner, Maike; Kufer, Verena; Brunner, Kathrin; Hartmann, Arndt; Amann, Kerstin; Agaimy, Abbas
<x xml:space="preserve">Abstract</x> Aims: Mesenchymal neoplasms of the kidney are rare, and most represent sporadic angiomyolipomas. A few haemangiomas have been reported in end‐stage renal disease (ESRD) but, to date, no study has focused on the frequency and morphological spectrum of mesenchymal lesions in ESRD. Methods and results: We evaluated retrospectively 90 nephrectomy specimens with ESRD. Haemangiomas were detected in eight cases (8.8%; six males and two females; mean age: 55 years); four were multifocal and four had concurrent renal epithelial neoplasms. Lesions involved the medulla (three), cortex (two) or both (three), and the size range was 1–25 mm (mean 4.8 mm). Histologically, all were capillary haemangiomas with an at least focally detectable spleen‐like anastomosing pattern. All tumours stained positively for CD31 and FLI‐1, but none expressed pankeratin (KL‐1), podoplanin/D2‐40, HHV8 or GLUT‐1. Minute angiomyolipomas (mean size 2.3 mm) were detected in four patients (mean age 49.5 years). Tumour‐like smooth muscle proliferations were seen surrounding muscular arteries (eight), occasionally admixed with fat extending from the renal sinus mimicking angiomyolipoma. No similar tumours were found in 105 control kidneys. Conclusions: Benign haemangiomas are not uncommon in ESRD, but may be under‐recognized. They display distinctive morphology and should be distinguished from angiosarcomas and capillary‐rich renal cell carcinomas.